HOW MARRIED AND UNMARRIED FEMALE STUDENTS OF KERALA DIFFERS IN THEIR ACADEMIC CONFIDENCE AND SUBJECTIVE WELL BEING? - Safiya ,Dr.A.Hameed, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The purpose of the present study was to find out whether there exists any significant difference in Academic Confidence and Subjective Well-being of female students of Kerala and to find out the relation between both. The sample of the study consisted of 100 female students who undergo various regular courses across Kerala. The data were collected using Academic Confidence Scale (Hameed & Safiya, 2017) and Subjective Well-being Inventory (Hameed & Safiya, 2017). The statistical analysis consisted of computation of Descriptive statistics, Mean Difference Analysis and Correlation Analysis. Result of the study shows that there exists no significant difference in Academic Confidence and Subjective Well-being of married and unmarried female students of Kerala with respect to marital as well as economic status and their Academic Confidence and Subjective Well-being are moderately correlated.